Аnticorruption culture in education - Jansaraeva, R.E.; Abdrakhmanov, D.S. (Bulletin of the Karaganda University “Law Series”, 2018)
The research theme is of high urgency due to the fact that nowadays one of the most important tasks is to stop the corruption in education for purpose develop quality of education in our country. Anticorruption culture is one of the components of legal culture. Corruption as a historical and political phenomenon is known for a long time, which even led to its perception as peculiar to the socium of objective reality. In modern Kazakhstan, it is increasingly manifesting itself in the status of a social phenomenon capable of jeopardizing all transformations and reforms. The problem of corruption has acquired a mass character today and has affected all spheres of public life. Of course, the main causes of corruption are political instability in the country, ineffective actions of power structures; imperfect legislation; low legal consciousness of the population; inaction of civil society institutions; a weak judicial system, inconsistent in the application of legislation. Foreign experience shows the successful use of anti-corruption propaganda tools in anti-corruption education, most often with the use of mass media. The media play a useful role in enhancing the citizens' anticorruption sense of justice, educating in society negative perceptions of corruption and at the same time being broadcasters of signals about the threat of punishment against potential corrupt officials. In our opinion, the anti-corruption culture of the individual is a system of knowledge, values, qualities and abilities that ensure the moral and psychological mood of the individual for rejecting and opposing corruption.